2021
DOI: 10.2106/jbjs.20.01904
|View full text |Cite
|
Sign up to set email alerts
|

Should Pertrochanteric and Subtrochanteric Fractures Be Treated with a Short or Long Intramedullary Nail?

Abstract: Objective: To compare major reoperations in elderly patients with pertrochanteric and subtrochanteric fractures receiving a short versus a long intramedullary nail (IMN). Design: Multicenter cohort studySetting: Eleven orthopedic departments across Denmark delivered data from the Danish Multidisciplinary Hip Fracture Registry (DMHFR) and review of healthcare records.Patients: Using surgical procedure codes for pertrochanteric and subtrochanteric fractures treated with IMN, the DMRHF was used to identify patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…This study also showed a failure rate of 0.97% for short PFNs and 0.52% for long PFNs. This is lower than other studies' estimates of 4%-4.1% for short nails and 3.2%-6.4% [11,19]. This may be due to the length of follow-up of our sample at 120 days compared to two years, which may not have captured all of the failures [11,19].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This study also showed a failure rate of 0.97% for short PFNs and 0.52% for long PFNs. This is lower than other studies' estimates of 4%-4.1% for short nails and 3.2%-6.4% [11,19]. This may be due to the length of follow-up of our sample at 120 days compared to two years, which may not have captured all of the failures [11,19].…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies from the 1990s [ 8 , 9 ] and a recent meta-analysis have shown a higher incidence of periprosthetic fractures in the short PFN cohort [ 10 ]. Other studies have shown a lower reoperation rate with short PFNs [ 11 , 12 ], and no statistically significant differences have been quoted in the rates of periprosthetic fractures in systematic reviews [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in results among these studies may be related to two main factors. First, plain radiograph-based classification studies underestimate fracture stability due to the difficulty in assessing the posterior osseous fragments, hence leading to possible errors in classification [ 11 , 17 , 19 ]. In our preliminary study, 20%-40% of A1-classified fractures using plain radiographs alone were reclassified as A2 using 3D CT scan images.…”
Section: Discussionmentioning
confidence: 99%
“…The first strength of this study is the use of a homogenous cohort with a complete set of two-directional plain radiographs and 3D CT scan images leading to higher reliability in fracture classification. The second strength of our study is that fracture classification was conducted by a single surgeon with knowledge of the revised AO/OTA classification system, effectively preventing misclassification, as may be seen in studies using national registries or mail-in systems [ 13 , 19 ]. It is usually difficult to detect the knowledge of reviewing surgeons, as this would greatly affect the reliability of classification between pertrochanteric and subtrochanteric fractures [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interlocking nails are considered by many to be the standard of care for stabilization of critical-sized bone defects (Rhorer, 2009;Dejardin et al, 2012;Shen et al, 2016;Flagstad et al, 2021;Kang et al, 2021;Viberg et al, 2021). Intramedullary fixation is commonly used for both rodent and large animal critical gap healing models (Lindsey et al, 2006;Schoen et al, 2008;Rhorer, 2009;MSc et al, 2013;Quirk et al, 2016;Shiels et al, 2018;Ozmeric et al, 2020).…”
Section: Introductionmentioning
confidence: 99%